Morphological study of nitrated stainless steels (2020)
Many of the components of engineering must be equipped with properties from the region adjacent to the surface of the component, since this is usually the place where the most severe loads are. Hard surfaces can be produced in many steel components by Thermo-chemically diffusion treatment as nitriding, carburizing, nitro-carburation and carbo-nitring, which are widely used in industry. This work shows the first results of morphology and mechanics study of AISI 420 steel surfaces and AISI H13 with plasma nitriding. The steel surface AISI 420 presents a greater roughness for the AISI H-13. From the mechanical point of view, the hardness for both steels presents an increase over 600%.